2019
DOI: 10.1371/journal.pone.0222122
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of an electrical stunning and chilling protocol for the slaughter of Atlantic mackerel (Scomber scombrus)

Abstract: Inducing unconsciousness in fish using electrical stunning prior to slaughter may improve fish welfare and fillet quality if such practises can be disseminated into wild capture fisheries. The objectives of this study were to: 1) evaluate if an established slaughter protocol consisting of dry electrical stunning (using a coupled AC/DC current at ≈ 110 V rms ) followed by chilling could be used to stun the wild captured species Atlantic mackerel ( Scomber scombrus )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…While electrical stunning is a euthanasia method approved by the Directive 2010/63/ EU [1] and is used for the euthanasia of larger fish [16][17][18][19][20], it is not commonly used in zebrafish laboratories [3,9]. This is the opposite to hypothermic shock, a method used by many facilities for the euthanasia of zebrafish [3,9], but not mentioned in the European Directive.…”
Section: Introductionmentioning
confidence: 99%
“…While electrical stunning is a euthanasia method approved by the Directive 2010/63/ EU [1] and is used for the euthanasia of larger fish [16][17][18][19][20], it is not commonly used in zebrafish laboratories [3,9]. This is the opposite to hypothermic shock, a method used by many facilities for the euthanasia of zebrafish [3,9], but not mentioned in the European Directive.…”
Section: Introductionmentioning
confidence: 99%
“…This will entail a re-design of single in-air/dry stunners such as the Crustastun™ to ones based on continuous flow or conveyer belt systems. Such systems exist for fish [ 25 , 26 ], but are still at the prototype stage for crustaceans [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include an initial effective anaesthetisation before killing [ 19 – 21 ] or a rapid stunning, either mechanical or electrical, that induces immediate insensibility by inactivating the nervous system [ 16 , 22 , 23 ]. Electrical stunning is used widely in the slaughter of domesticated farm animals [ 24 ], and can also be effective on aquatic animals such as fish [ 25 , 26 ]. It therefore seems to offer potential for humane killing of decapod crustaceans, and indeed a number of stunning devices have been developed for this purpose: LAVES (adapted from a fish stunner) [ 27 ], STANSTAS [ 28 ] and CRUSTASTUN™ [ 16 , 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evidenced vertebral fractures and consequent blood spots in fillets of fishes exposed to electrical stunning, which negatively affect fillet quality. 19,51 Conversely, other authors did not evidence spinal damage or haematomas as post-filleting quality imperfections, 11,52,53 indicating that this method was properly applied in terms of voltage and exposure time. In the present study, 55% of ES fillets showed haematomas at 0 h, in line with what was observed in Chinook salmon (24-71%) 51 and Atlantic herring (60%), 19 hence highlighting the need to set specific electrical stunning parameters for S. carpio.…”
Section: Fillet Shape and Colour Changesmentioning
confidence: 93%